Why do not people attend football matches in Hungary? - Balogh, Renátó; Kardos, Magdolna Valentina; Bácsné Bába, Éva (International Journal of Engineering and Management Sciences, 2021)
Both international and domestic research on passive sport consumption focuses on the motivations of fans. However in Hungary, unlike the examples of North America and Western Europe, we have to look for answers to the question of why people do not go to football matches. In order to find an answer to this question, we conducted an online survey with a number of items of 347 people. For the latter a scale measuring absence from sport consumption was used and the reliability of the scales was tested by Cronbach’s alpha calculation. After our principal component analysis, we developed 5 internal and 5 external factors, on which we conduct hypothesis test along demographic and sports consumption variables. Based on our results, we have established that, contrary to public opinion, the low number of spectators in Hungarian football matches is not only and primarily due to unsucces and the low quality of matches. Our respondents are mostly kept away from stadiums by football-related government measures, as well as by preferring to participate in other recreational program opportunities.